The view of the otherness in Una excursión a los indios ranqueles, by Lucio V. Mansilla - María Lydia Polotto Sabaté (Miscelánea Comillas, 2013)
In this article we will try to tackle how the Argentinean identity has beenbuilt-up, since the end of the 19th century, by the denial of the «otherness». This observation will be made by analyzing Lucio Mansilla’s book Una excursión a los indios ranqueles. We will also make inquiries on the violence that is exerted from the use of the language focused on the annulment of the Other and how does that Other has been displaced throughout the History in different social agents. To finalize, we will consider how nowadays Occidental World imposes its mental models to exert a cultural influence to monopolize and homogenize the ideological speech on identity and values.